What Shapes the News Around the World? How Journalists in Eighteen Countries Perceive Influences on Their Work - Mellado-Ruiz, C (2011)
This article compares the perceived importance of influences on news work across 18 societies. Evidence is based on journalists survey responses to a six-dimensional scale, covering political, economic, organizational, professional, and procedural influences as well as influences from reference groups. The results confirm the expectation that political and economic factors are clearly the most important denominators of cross-national differences in the journalists perceptions of influences. Furthermore, perceived political influences are clearly related to objective indicators of political freedom and ownership structures across the investigated countries. Economic influences seem to have a stronger impact in private and state-owned media than in public newsrooms, but they are not related to a country s economic freedom. With respect to organizational, professional, and procedural influences as well as the impact of reference groups, the differences between the countries turned out to be much smaller. © The Author(s) 2011.